Evolving approaches to the economics of public policy : views of award-winning economists - Kimmel, Jean (W.E. Upjohn Institute for Employment Research, 2016)
Five award-winning economists tackle a diverse range of topics and show how applied economics has evolved to give policymakers a more nuanced approach to policy development.